PEMBERDAYAAN PETANI KELAPA DI DESA SUNGAI RENGAS - A’ang Kurniawan E.01107053 (PublikA, Jurnal Ilmu Administrasi Negara, 2014)
The problem in this research is the system and palm agribusiness in Sungai Rengas not develop optimally and performance between the nodes is not well integrated agribusiness. Other problem is socialization and increase citizen knowledge about coconut, how to grow crops and coconut maintenance way to use science and technology has not been done. Besides, from the government has not provided an alternative solution more favorable to farmers. This study aims to describe the efforts of agencies involved in public awareness Sungai Rengas coconut farmers in order to have the ability, skills and expertise and. The results showed that the efforts of relevant agencies in the wake of coconut farmers Sungai Rengas to have the ability, skills and expertise, and basically good enough. However, in the implementation of nine coconut farmer empowerment program could only be three points which can be carried out in the village of River Rengas, and even then its implementation is not optimal. These three points are, among others, education and community training, counseling and mentoring activities and institutional strengthening farmers. Based on the research findings that the constraints in the coconut empower farmers in Sungai Rengas is the limited budget and the number of extension workers companion. Responding to the suggestion that the phenomenon exists recommended that coconut farming community empowerment is an ongoing process that empowerment evaluation should be done gradually starting from before the program is executed, the initial implementation of the program, and periodic evaluation after implementation of the program, it is necessary to study more about the empowerment evaluation each stage in the implementation of the empowerment. Keywords: Empowerment, Coconut Farmers